An evaluation of farmers' digital literacy and awareness on the adoption and implementation of bundled digital innovations in Uganda - Ogutu, Sylvester; Kikulwe, Enoch; Ajambo, Susan; Ategeka, Stewart; Birachi, Eliud (International Food Policy Research Institute, 2024)
Global agri-food systems face numerous challenges, including the adverse effects of climate change, low productivity, limited adoption of technologies, and restricted access to input and output markets. These constraints contribute to increased food insecurity, decreased income from agriculture, and stagnated growth rates in many agrarian economies. Digitizing the agriculture sector presents a sustainable solution to these challenges by providing critical information that supports optimal decision-making, enhancing efficiency and productivity. However, the widespread adoption of digital innovations in this sector is hindered by low awareness of existing technologies, limited digital literacy, and prevailing social norms and power dynamics affecting various population segments, particularly women and youth.